2015
DOI: 10.5487/tr.2015.31.3.279
|View full text |Cite|
|
Sign up to set email alerts
|

Distribution of Seven N-Nitrosamines in Food

Abstract: N-nitrosamines, which are classified as carcinogens by IARC and US EPA, can be easily found in various foods. They are reaction products between nitrogen oxide and secondary amines, but can also be generated during fermentation. Ever since the 1960s, when nitrite, used as a preservative in processed meats, was suspected to generate N-nitrosamines, the usage of the food additive has been debated. However, the benefit of nitrite in food supply could not be ignored and the risk-benefit analysis has become a key i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(93 citation statements)
references
References 21 publications
3
86
0
4
Order By: Relevance
“…In several studies, a Western diet (high in animal protein and fat, low in fiber) led to a marked decrease in numbers of total bacteria and beneficial Bifidobacterium and Eubacterium species [26, 29, 48]. Consumption of a Western diet has also been associated with production of cancer-promoting nitrosamines [123, 124].
Fig.
…”
Section: Diet and Microbiotamentioning
confidence: 99%
“…In several studies, a Western diet (high in animal protein and fat, low in fiber) led to a marked decrease in numbers of total bacteria and beneficial Bifidobacterium and Eubacterium species [26, 29, 48]. Consumption of a Western diet has also been associated with production of cancer-promoting nitrosamines [123, 124].
Fig.
…”
Section: Diet and Microbiotamentioning
confidence: 99%
“…Some reduction of the total Nnitrosamine content in DFSs appeared to be possible through the addition of ascorbic acid [42]. A large number of agricultural food products, seafoods, meat products, vegetable oils, sauces, and seasonings contain N-nitrosamines in the range 0.2 to a few g/kg [43]. A benchmark dose methodology for developing tolerable daily intakes (TDIs) has been developed based on a large lifetime cancer dose-response study of NDMA in drinking water given to rats [44].…”
Section: 3mentioning
confidence: 99%
“…As shown in Table , the concentration of NOCs in cooked beef, pork, and fish ranged between 1.8 and 5.0 µg/g, and comparisons between cooking methods showed the highest concentration with the firewood‐grill method. Park, Seo, Lee, and Kwon () reported that NDMA concentrations in processed meats, such as sausages, hams, and bacons, ranged from 0.31 to 1.54 µg/kg, lower than the concentration found in vegetables and fruits.…”
Section: Potential Harmful Substances Produced During Cooking and Promentioning
confidence: 98%